Constituents of a hit parade: Questioning democracy and listener participation in P4 i P1’s Det elektriske barometer - Abildgaard, Mette Simonsen; Jensen, Erik Granly (MedieKultur: Journal of media and communication research, 2014)
Due to their historically inaccessible nature, public service broadcasters’ media archives have lent themselves primarily to internal refl ection while historical contextualisation of the cultural heritage in these archives has been broadcasters’ prerogative. In this study, digitised material from the Danish youth radio programme P4 i P1’s Det elektriske barometer forms the basis for an experiment into how access to digital archives can inform humanities scholarship. We argue that one important implication of the new digital archives is that they enable approaches independent of broadcasters’ own narratives since they off er the possibility for autonomous study of large quantities of material. The character of listener participation in Det elektriske barometer, which had the slogan ‘the listener-determined hit parade’, is approached from a micro-, meso-, and macro-level employing Carpentier’s concept of participation (2011b), to explore how diff erent approaches to digital archives can provide new answers to media’s self-presentation.